THE PROFILE OF EFL TEACHERS’ CRITICAL THINKING ON PROFESSION DESCRIPTORS - Alda Swarni Dewi; maliqul hafis; Finny - Anita; Rahayu - Melia sari (IKIP PGRI Pontianak, 2021)
This research aimed to explore the average score of senior secondary school EFL teachers’ critical thinking on profession descriptors in Kabupaten Kayong Utara. The design of this research is descriptive study in which the total sample are 10 EFL teachers determined by homogenous purposive sampling that is taken the full time in service teachers or civil servants only. This research used an online critical thinking skill test in reading and alternative choices form as data collection tools which consisted of 16 questions, specifically for inference, assumptions, deductions, interpret the information and evaluate the arguments in a row are 4, 4, 2, 2 and 4 questions. Data have been collected then are specified into categories of skills based on the average score. The research findings indicated that the EFL teachers’ critical thinking skills in category of highly skilled in 57,5%. Based on the results, it can be concluded that the EFL teachers’ critical thinking in North Kayong is proficient.Keywords: EFL teachers, critical thinking, profession descriptors.